Invasividade de Hedychium coronarium J. Köenig (Zingiberaceae) em diferentes umidades do solo - Almeida, Renata Vilar de (2015)
Biological invasion is a threat to biodiversity, due to competition for resources between invaders and native organisms, decreasing the overall biodiversity. So, studies about the invasiveness of the ecossystems and invasion potential of exotic plants several environments must be taken to control this species. Hedychium coronarium, from the Himalayas, is an example of a high invasivisiness plant, taken to different places in the world, mainly due to ornamental uses. This study evaluated the development (height, diameter, birth and ramets mortality and internal rhyzome anatomy) of plants under different moisture contents, in in situ and in vitro experiments. We found the existence of plasticity for both vegetative ramets growth, and the internal rhyzome anatomy, which may contribute to the invasive potential of this plant.